Eye Lens Dosimetry in Interventional Radiology: Assessment With Dedicated Hp(3) Dosimeters. Issue 2 (May 2021) - Merrachi, Nassim-Albert; Bouchard-Bellavance, Roxanne; Perreault, Pierre; Gilbert, Patrick; Soulez, Gilles; Bouchard, Louis; Oliva, Vincent L.; Giroux, Marie-France; Normandeau, Lysanne; Therasse, Eric
Purpose: To quantify eye lens dose in interventional radiology and assess whether neck dosimeter is a good surrogate to evaluate eye lens dosimetry. Methods: Radiation exposure was prospectively measured in 9 interventional radiologists between May and October 2017. Standard Hp(0, 07) thermoluminescent dosimeters (TLDs) were worn at the neck outside the lead apron, and 2 dedicated eye lens Hp(3) TLDs were placed just above the eyes, one midline and another at the outer edge of the left eye. Correlations between eye lens and neck TLD doses were assessed with Pearson coefficient, and linear regression was used to predict eye lens dose from neck TLD values. Results: Eye lens dose without eye protection was 0.18 ± 0.11 (mean ± standard deviation; 0.08-0.41) mSv per workday and 35.3 ± 6.6 mSv (16.3-82.9) annually (200 workdays/year). Five (56%) radiologists exceeded the 20 mSv annual eye lens dose limit. Eye lens doses from left and central TLDs were 12.46 ± 3.02 and 9.29 ± 3.38 mSv, respectively ( P = .027). Mean eye lens (left and central) and neck TLD doses were 10.87 ± 2.67 and 16.56 ± 5.67 mSv, respectively ( P = .008). Pearson correlation coefficient between both eye lens TLD and between mean eye lens TLD and neck TLD doses were 0.91 and 0.92, respectively. Average of eye lens dose was 0.0179 + (0.5971 × neck dose). Conclusion: Full-time interventional radiologists are likely to suffer from deterministic radiation effects to the eye lens, especially on the left side. Neck TLD significantly overestimates eye lens dose. However, eye lens doses are highly correlated with neck doses and may be predicted from the neck TLD values.